Assessment of knowledge on vaccination among mothers of under five children: An observational study - V. TAMIZHKODI, (International Journal of Pharma and Bio Sciences, 2019)
Immunity is the resistance offered by the host to fight against the harmful effects of a pathogenic microbial infection. A person is said to be immune when he / she possess specific protective antibodies or cellular immunity as a result of previous infection or immunization. One of the factors contributing to under five mortality is the lack of awareness about child care. Immunization aim is to protect individual from infectious diseases. Immunization operates like an early morning system. It prepares the body to fight against infection. Live injected vaccines, the first dose administered at the recommended age usually provides protection. Additional dose is to ensure zero conversion. The main aim of this study is to assess the knowledge regarding special vaccine among mothers of under five children in urban community. Non - experimental research design was used for this study. Simple random technique was adopted for this study. For the study, 30 samples of mothers of under-five children were taken. The results showed Majority, 21 (70%) of them had moderate knowledge, 6(20%) of them had inadequate knowledge, 3(10%) of them had adequate knowledge regarding vaccine.